A Conceptual Framework for Customer-Centric Strategic Approach for Competitive Advantage with Specific Reference to Super Market Retailers in India - Shenoy, Seema S.; Sequeira, A. H.; K., Devaraj (Indian Journal of Marketing, 2012)
Supermarket retailers in India are amidst fierce competition from not just their Indian counterparts, but also from strong foreign players. The only way out for survival is through attainment of competitive advantage. Though competitive advantage has always been at the heart of firms operating in the increasingly competitive retail environment, the concept of competitive-centric retail strategy is slowly losing ground in terms of its effectiveness in enabling Indian supermarket retailers to attain a competitive advantage. In view of the same, this paper attempts to devise a conceptual framework on customer-centric retail strategy for enabling supermarket retailers to attain a competitive advantage. The influence of intervening variables that have added to the need for attaining a competitive advantage have been considered and the performance outcomes of employing the customer-centric strategy have also been detailed in this paper.